2016
DOI: 10.1002/ijc.30041
|View full text |Cite
|
Sign up to set email alerts
|

PKM2 uses control of HuR localization to regulate p27 and cell cycle progression in human glioblastoma cells

Abstract: The M2 isoform of pyruvate kinase (PK) is upregulated in most cancers including glioblastoma. Although PKM2 has been reported to use dual kinase activities to regulate cell growth, it also interacts with phosphotyrosine (pY)-containing peptides independently of its kinase activity. The potential for PKM2 to use the binding of pY-containing proteins to control tumor growth has not been fully examined. We here describe a novel mechanism by which PKM2 interacts in the nucleus with the RNA binding protein HuR to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
(115 reference statements)
2
27
0
Order By: Relevance
“…Dysregulation of p27Kip1 gene expression at the mRNA or the protein level was reported in various cancers [39,40]. Especially, p27Kip1 has been implicated in tumorigenesis and oncogenic progression of gliomas [41,42]. Here we provide evidence that p27Kip1 is a transcriptional target of EYA4, and its expression can be suppressed by EYA4 in glioma cells.…”
Section: Discussionsupporting
confidence: 51%
“…Dysregulation of p27Kip1 gene expression at the mRNA or the protein level was reported in various cancers [39,40]. Especially, p27Kip1 has been implicated in tumorigenesis and oncogenic progression of gliomas [41,42]. Here we provide evidence that p27Kip1 is a transcriptional target of EYA4, and its expression can be suppressed by EYA4 in glioma cells.…”
Section: Discussionsupporting
confidence: 51%
“…Firstly, HUR acts as a positive effector for gene expression by binding and stabilizing their mRNA, for example cyclooxygenase 2, p21 and cyclin D1 (31)(32)(33). Secondly, HUR can decrease the translation efficiency of mRNA, including of TNF-Îą and p27 (34,35). The results from the present study demonstrated that HUR protein level was increased in primary breast cancer tissues compared with adjacent normal tissues, and that this effect was accompanied by increased BCL-2 expression and decreased BAX expression.…”
Section: Discussionmentioning
confidence: 50%
“…Also, miR‐7 and miR‐219 influence voltage‐gated K + channels, NMDA‐type receptors, and intracellular Ca 2+ , potentially altering neuronal circadian rhythms (Mehta and Cheng, 2013). Like the circadian clock mechanism, evidence indicates ELAVL1 is regulated by pyruvate kinase in glioblastoma cells (Mukherjee et al, 2016), suggesting another way that energy demands within the organism might also alter SCN cell networks. Alternatively, ELAVL1 may serve in a non‐clock function in the SCN by preventing excitotoxic damage though intracellular Ca 2+ (Skliris et al, 2015); the SCN is unique among hypothalamic nuclei in receiving substantial glutamatergic retinal afferents, and protection from excessive sensory stimuli would be expected.…”
Section: Discussionmentioning
confidence: 99%